Ganoderma boninense basal stem rot induced by climate change and its effect on oil palm - Abubakar, Ahmed; Ishak, Mohd Yusoff; Abu Bakar, Aisyah; Uddin, Mohd Kamal (Springer, 2022)
In countries like Malaysia and Indonesia, palm oil is a strategic commodity. A wide variety of products are made from palm oil, including food, cosmetics, as well as biodiesel production. It generates export revenues and helps many economies, especially Indonesia and Malaysia. The production of oil palm is influenced by both the changing climate and the prevalence of pests and diseases. Ganoderma boninense, the white rot fungus, is presently recognised as a significant barrier to the hugely profitable oil palm industry, especially in Southeast Asia and the rest of the production regions. The objective of this review is to examine the impact of G. boninense on oil palm production as induced by climate change. According to the findings of this review, when temperatures rise by 1–4 °C, oil palm yield declines by 10–41% and causes water stress in the palms. Ganoderma basal stem rot affects different parts of palm trees, resulting in a decrease in fresh fruit bunch yield as well as ecological and economic damage. G. boninense affects oil palm more noticeably in Malaysia and Indonesia, resulting in economic losses to farmers and reduced revenue to governments. Climate change projections indicate that G. boninense will have a greater impact on oil palm in the future, particularly from 2050 onwards. In Sumatra, some parts of Malaysia, and other oil palm growing regions, G. boninense is predicted to have a 41–100% impact by 2100. This study recommends appropriate selection of planting area, planting improve variety, best soil management practices, biological control, and the application of biotechnology. These will help in planning for climate change as well as the control and management of G. boninense.